Analisis Pengelolaan Alokasi Dana Desa Di Kecamatan Kema Kabupaten Minahasa Utara - Kesek, Meilany; Ilat, Ventje; Warongan, Jessy (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2019)
Abstract. This study aims to analyze the management of village fund allocation in Kecamatan Kema North Minahasa Regency. This is a qualitative research with a case study approach. Data were obtained through in-depth interview techniques and documentation studies. The key informant is determined purposive sampling to obtain precise and accurate information results. The criteria of the informant is the old law of the village, the village secretary, village treasurer and village consultative body. In-depth and semistructured interviews were conducted . The triangulation method was used to test validity testing or data credibility and data source. Data were transcribed and analyzed. Themes/codings and the conceptualisation of the scientific statement were gained from the analysis. The interpretation results are inferred in narrative text. The results showed that the process of managing village funds allocation from planning, implementation, reporting and accountability were implemented consistently and accordingly with Permendagri 113 year 2014. There are only a few constraints for example in regulation. Regulation governing the planning process is not in accordance with the basic needs of priorities in each village, the limitation of knowledge and understanding of human resources, ineffective communication between the old laws of the village with other village devices and between the village's old law and society. Thus, the regulation should be enforced before the implementation of the village, hence Â the proposal to the establishment of APBDesa would be implemented accordingly to the situation and conditions in the village. If this had happened, the planning process could answer the basic needs of priorities in Village, the local government should be more effective. Furthermore, they also should socialize and guide the village aparatus staff, in this case, the village treasurer should be informed and taught about SISKEUDES. Keywords: Village fund allocation management, village fund allocation constraintsAbstrak. Dalam penelitian ini bertujuan menganalisis Pengelolaan Alokasi Dana Desa di Kecamatan Kema Kabupaten Minahasa Utara. Metode penelitian menggunakan kualitatif dengan pendekatan studi kasus. Data diperoleh melalui teknik wawancara mendalam dan studi dokumentasi. Informan kunci ditentukan secara purposive sampling untuk mendapatkan hasil informasi yang tepat dan akurat. Kriteria informan adalah Hukum tua desa, Sekertaris desa, Bendahara desa dan Badan permusyawaratan desa. Wawancara menggunakan in-depth interview jenis semi terstruktur. Metode triangulasi digunakan dalam pengujian validitas atau kredibilitas data dan sumber data. Data transkrip yang diuraikan dari hasil wawancara di analisis dengan metode analisis kemudian diberi tema/ coding dan dilakukan konseptualisasi pernyataan ilmiah. Hasil interpretasi disimpulkan dalam teks naratif. Hasil penelitian menunjukkan bahwa dalam proses pengelolaan Alokasi Dana Desa mulai dari perencanaan, pelaksanaan, pelaporan dan pertanggungjawaban sudah mengacu pada Permendagri 113 Tahun 2014 hanya terdapat beberapa kendala misalnya pada regulasi. Regulasi yang mengatur pada proses perencanaan tidak sesuai dengan kebutuhan dasar prioritas yang ada di setiap desa, keterbatasan pengetahuan dan pemahaman sumber daya manusia, komunikasi yang tidak efektif antara hukum tua desa dengan perangkat desa lainnya maupun antara hukum tua desa dengan masyarakat. Dengan demikian seharusnya regulasi turun sebelum dilaksanakannya musrembang desa sehingga pada saat usulan sampai pada penetapan APBDesa sesuai dengan situasi dan kondisi yang ada di desa supaya proses perencanaan dapat menjawab kebutuhan dasar prioritas di desa, pemerintah daerah harus lebih efektif serta mengadakan sosialisasi dan bimbingan kepada perangkat desa dalam hal ini bendahara desa tentang SISKEUDES.Kata Kunci: Pengelolaan Alokasi Dana Desa, Kendala Alokasi Dana Desa